1988
DOI: 10.1126/science.2838905
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Transcription Factors and Regulation of IL-2 Receptor Gene Expression by HTLV-I tax Gene Product

Abstract: Expression of the interleukin-2 receptor (IL-2R alpha) gene is activated by the transcriptional activator protein, Tax (previously referred to as the tat gene product), encoded by the human T-cell leukemia virus (HTLV-I). Multiple protein binding sites for specific DNA-protein interactions were identified over the upstream IL-2R alpha transcriptional regulatory sequences. However, only one region, which includes the sequence motif GGGGAATCTCCC, was required for activation by both the tax gene product and mitog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
223
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(227 citation statements)
references
References 39 publications
3
223
0
1
Order By: Relevance
“…Tax usurps signaling pathways, including NF-kappa B [90], leading to the up-regulation of numerous cytokines and cytokine receptors. Remarkably, Tax has been shown to up-regulate expression of IL-2 and IL-2Ra chain [91,92] as well as IL-15 and IL-15Ra chain [93,94], suggesting that an autocrine/paracrine mechanism could be involved in proliferation of ATL cells in early stages of infection [95]. Of note, recent studies have found that the viral protein p12 stimulates production of IL-2 in activated T-cells [96], interacts with the IL-2 receptor b chain, and stimulates the Jak/STAT5 pathway and T-cell proliferation [97].…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…Tax usurps signaling pathways, including NF-kappa B [90], leading to the up-regulation of numerous cytokines and cytokine receptors. Remarkably, Tax has been shown to up-regulate expression of IL-2 and IL-2Ra chain [91,92] as well as IL-15 and IL-15Ra chain [93,94], suggesting that an autocrine/paracrine mechanism could be involved in proliferation of ATL cells in early stages of infection [95]. Of note, recent studies have found that the viral protein p12 stimulates production of IL-2 in activated T-cells [96], interacts with the IL-2 receptor b chain, and stimulates the Jak/STAT5 pathway and T-cell proliferation [97].…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…The activity of these proteins, which activate expression of genes participating to the immune and in¯ammatory responses, is regulated mainly through cytoplasmic retention. Expression of Tax in lymphocytes induces a permanent presence of the NF-kB/Rel factors in the nucleus (Ballard et al, 1988;Leung and Nabel, 1988;Ruben et al, 1988). This e ect is likely to result from an activation of the proteolytic processing of the inhibitory molecules IkB-a (Lacoste et al, 1995), IkB-b (Good and Sun, 1996) and NF-kB1 p105 .…”
Section: Introductionmentioning
confidence: 99%
“…The a-chain of the IL-2 receptor (IL-2Ra) was the first cellular gene reported to be upregulated by Tax (Ballard et al, 1988;Ruben et al, 1988). Together with b-and a common g-chain, IL-2Ra forms the high-affinity IL-2 receptor, which permits signaling at low IL-2 concentrations.…”
Section: Il-2 and Il-15mentioning
confidence: 99%